Human Influence on Desertification of Northeast Khorasan Province, Iran - Garivani, G M; Mokhanoy, E N; Shahandeh, H (Annals of Arid Zone, 2016)
Map of desertification process in the northern Khorasan region was compiledadopting methodology of FAO-UNEP and criteria devised by the Desert Instituteof Turkmenistan for arid, and semi-arid regions. Based on Landsat-TM data, adesertification map of the region in 1972 was prepared and compared with human-induceddesertification map compiled for northern Khorasan in 1999. -SoiL geologicaLtopographic, climatic, agricultural, and sociological information were incorporatedin compiling these maps. Data collected show that about 87% of the northernKhorasan region is affected by desertification, of which 55% is severely and veryseverely desertified. Around 6% of the area is not affected by desertification and8% is a natural desert. The degradation of vegetation cover caused by human activitiesis the most extensive form of desertification, followed by water erosion, secondarysalinization, and wind erosion. These cover 47%, 34%, 6%, and